The Effect of Simvastatin Treatment on Plasma Steroid Levels in Females with Non-classic Congenital Adrenal Hyperplasia - Krysiak, R.; Okopien, B. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Non-classic congenital adrenal hyperplasia (NC-CAH) is one of the most frequent genetic disorders and its presence often results in androgen excess. 4 females with coexisting symptomatic NC-CAH and isolated hypercholesterolemia and 11 sex- and weight-matched control subjects with elevated cholesterol but normal steroid levels, participating in our study, were treated with simvastatin (20 mg daily). Throughout the whole period of simvastatin treatment, plasma levels of 17-hydroxyprogesterone, testosterone, androstendione and dehydroepiandrosterone sulfate in patients with NC-CAH remained lower compared with baseline, but increased in 2 patients after withdrawal of this drug. No changes in plasma steroids were observed in simvastatin-treated control subjects. Our findings suggest that simvastatin treatment may bring some benefits to symptomatic female patients with NC-CAH.
Keywords: adrenal cortex; congenital adrenal hyperplasia; androgens; statins